Perspektif Ekonomi Islam: Dampak Keberadaan Kawasan Industri Cikarang Pada Peningkatan Kesejahteraan Masyarakat - MH Ainulyaqin; Adrianna SR; Listian I. Achmad; Sukron Mamun; Andri Jaelani (Jurnal Ilmiah Ekonomi Islam, 2025)
This research aims to analyze the impact of the presence of the Cikarang Industrial Estate on the improvement of the welfare of the community in Bekasi Regency from the perspective of Islamic economics. This research uses a qualitative descriptive method with data collection techniques through interviews and documentation. The respondents in this research are the community living around the Cikarang Industrial Estate, and there are several key informants involved in the development of the Cikarang Industrial Estate. The results of the research show that the presence of the Cikarang Industrial Estate has both positive and negative impacts on the improvement of the welfare of the community in Bekasi Regency. The positive impacts include increased employment opportunities, increased income, and improved infrastructure development around the industrial estate. On the other hand, the negative impacts include the shifting of jobs from the agricultural sector to the industrial sector and environmental damage. From the perspective of Islamic economics, the presence of the Cikarang Industrial Estate needs to be analyzed in terms of social and moral aspects in economic activities, emphasizing the importance of justice, equality, and sustainability in economic activities. Therefore, the development of the Cikarang Industrial Estate needs to be carried out in accordance with the principles of Islamic economics to optimize economic benefits and minimize negative impacts on the community.